2015
DOI: 10.18011/bioeng2015v9n3p268-278
|View full text |Cite
|
Sign up to set email alerts
|

Seleção De Subamostras De Feijão-Fava Para Resistência À Antracnose

Abstract: RESUMOObjetivou-se nesse experimento, com uso de folhas destacadas, selecionar subamostras de feijão-fava resistentes ou com algum grau de resistência à antracnose visando contribuir para elevação da produtividade da cultura. As folhas foram inoculadas aos 40 dias após a semeadura, onde é possível selecionar folhas uniformes, com uma suspenção de esporos do Colletotrichum truncatum. A severidade foi avaliada visualmente por dois avaliadores aos cinco e sete dias após a inoculação (DAI), utilizando uma escala d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
1
0
2
Order By: Relevance
“…This is an indication of homogeneity of inoculation of the isolates in the lima bean accessions and that all accessions inoculated were infected by C. truncatum. Similar results were observed by Carmo et al (2015) and Santos et al (2015), who observed anthracnose symptoms on detached leaves of lima bean, started from the third to fourth DAI and severity evaluations were performed at five and seven DAI. However, extensive disease variations has been reported, such as C. truncatum-induced symptoms in susceptible lentil (Lens esculenta Moench) cultivars varying from three to six days and up to 14 DAI in resistant cultivars (CHONGO;GOSSEN;BERNIER, 2002).…”
Section: Reaction Of the Lima Bean Accessionssupporting
confidence: 86%
See 2 more Smart Citations
“…This is an indication of homogeneity of inoculation of the isolates in the lima bean accessions and that all accessions inoculated were infected by C. truncatum. Similar results were observed by Carmo et al (2015) and Santos et al (2015), who observed anthracnose symptoms on detached leaves of lima bean, started from the third to fourth DAI and severity evaluations were performed at five and seven DAI. However, extensive disease variations has been reported, such as C. truncatum-induced symptoms in susceptible lentil (Lens esculenta Moench) cultivars varying from three to six days and up to 14 DAI in resistant cultivars (CHONGO;GOSSEN;BERNIER, 2002).…”
Section: Reaction Of the Lima Bean Accessionssupporting
confidence: 86%
“…There was no identification of material with no symptoms, but it was possible to distinguish differentiated levels of resistance (Figure 2). Similar results were obtained by Cavalcante et al (2012), among the reactions caused by 30 subsamples of C. truncatum and by Santos et al (2015), with the reaction of 57 subsamples of lima bean to the severity of the anthracnose in detached leaves.…”
Section: Reaction Of the Lima Bean Accessionssupporting
confidence: 82%
See 1 more Smart Citation
“…Observou-se também a presença de manchas foliares nas testemunhas, variando de 0,00 a 1,00 (avaliação visual) e de 0,00 a 1,88 (avaliação Asses 2.0). Resultados similares foram encontrados nas avaliações da reação de feijão-fava a C. truncatum com folha destacada, realizado por Cavalcante et (23). Em tais estudos foi constatada uma alteração de comportamento dos acessos na avaliação de 5 DAI para 7 DAI, atribuída ao comportamento hemibiotrófico do fungo.…”
Section: Caracterização Fitopatológicaunclassified
“…No Nordeste do Brasil, pesquisas que envolvem a seleção de acessos de feijão-fava foram realizadas com técnica de inoculação a partir de folhas destacadas, sendo estas selecionadas apenas em um estágio fenológico (3,4,6,23). Se constituindo assim em uma limitação quando se pretende selecionar acessos resistentes, pois no patossitema Phaseolus vulgaris L. e Colletotrichum lindemuthianum Sacc.…”
unclassified